PENGEMBANGAN E-MODUL MATEMATIKA MENGGUNAKAN LIVEWORKSHEETS SEBAGAI BAHAN PEMBELAJARAN MANDIRI PADA MASA PANDEMI COVID-19 - Fitriani Roskaputri; Mardiyana Mardiyana; Laila Fitriana (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
This study aims to find out the validity and practicality of mathematics e-module based on the “Liveworksheets” website as the students’ independent learning material in this pandemic era of COVID-19. This study is a Research and Development (R&D) employing a 4D developmental model. The assessment of the product was conducted based on the validity and practical aspects. The data were obtained from the expert validation to assess the validity, and the teacher's and students’ questionnaires to assess the practicality. The validity was assessed by 3 experts of material and media aspects. Meanwhile, the practicality was assessed by involving 25 tenth-grade students and 2 mathematics teachers of SMA Negeri 8 Kota Pontianak. The results of the study showed that 1) based on the expert validation, this e-module was categorized as very valid for material aspect and as valid for media aspect, 2) based on the questionnaire for assessing the practicality, it showed that this e-module was very practical to use based on students’ responses and as practical based on the teachers’ responses. Viewed from the results of validity and practicality assessment, this e-module based on the “Liveworksheets” website is able to be used as an independent learning material in this pandemic era of COVID-19